Respostas
respondido por:
0
(A)
√4 + √9 ||||||||||||| √4 + 9
2 + 3 |||||||||||||||||||| 2 + 9
5 |||||||||||||||||||||||||||| 11
(B)
√25 - √9 |||||||||||||||||||||||| √25 - 9
5 - 3 ||||||||||||||||||||||||||| 5 - 9
2 |||||||||||||||||||||| - 4
respondido por:
2
Mostra que:
A)
√4 + √9 igual √4 +9
√4 + √9 = √4 + 9
2 + 3 = 2 + 9
5 = 11 (INCORRETO)
5≠ 11 ( diferente)
B)
√25 - √9 igual √25 - 9
√25 - √9 = √25 - 9
5 - 2 = 5 - 9
3 = - 4 ( INCORRETO)
3 ≠ - 4 ( DIFERENTE)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás